SECCODES - Secure Communication Development System. - Mario Tadashi Shimanuki (2003)
In the history of telecommunications, there has been no single piece of terminal equipment so widely used as the telephone. In many parts of the world, the characteristics of being simple to operate, cheap to purchase and inexpensive to use, and the freedom to access almost any other terminal across the globe, have made the fixed line telephone a basic need in life. As far as the telephone is concerned, there is little personal privacy on telephone conversations; it is easy for an agency or an individual to monitor private telephone lines. If there is a need to protect the telephone communication, there are several steps to be taken and technologies to be employed. In this sense, this thesis concerns the study and implementation of a Secure Communication Development System (SECCODES), so two parts can exchange classified or sensitive information via a telephone line. The analog voice is digitized and encoded by the VC-20 AMBE-MR voice codec into a 4.8 kbps data bit stream; it is processed and encrypted by a Nec V25 processor to be transmitted to a telephone line by a modem. If one has a need or desire to protect his/her telephone communication, SECCODES is suitable to have a secure speech (confidentiality), in this context, the cipher and decipher blocks were designed focusing the easiness to change the parameters and the cryptography algorithm.